A qa2+-pGEM vector for Neurospora transformations - M. A. Nelson; R. L. Metzenberg (Fungal Genetics Reports, 1992)
The qa-2+ gene has been widely used as a selectable marker in Neurospora transformations (Akins and Lambowitz 1985. Mol. Cell. Biol. 5:2272-2278). A plasmid (pMSN1) has been constructed to facilitate the cloning of selected genes into a qa-2+ vector. The system takes advantage of the blue/white screening possible when cloned fragments are inserted into the E. coli lacZ (beta-galactosidase) gene, and also facilitates subsequent sequencing of the cloned genes.